Analisis Preferensi Mahasiswa Jakarta Terhadap Kartu Layanan Prabayar GSM - Ronald Sukwadi; Mellisa Mellisa (Universitas Bunda Mulia, 2017)
The global market for telecommunication industries is expanding rapidly. This situation has also increased the competition among prepaid card service providers in this sector. In order to retain the customer, the service providers must be able to identify the customer needs. In this study, conjoint analysis is applied to examine the service attributes that become the student’ preferences in choosing prepaid cards. Then, the cluster analysis is used to group the preferences based on the demographic aspects. The results show that the operator and signal strength are the most important service attributes for the students in Jakarta.Keywords: Preference, Prepaid Card Services, Conjoint Analysis, Cluster Analysis.